Effect of different accessions on yield contributing characters and yield of strawberry under different growing condition - Alam, Md Shamsul; Islam, Md Rafiqul; Afrin, Sadia (Research in Agriculture Livestock and Fisheries, 2019)
An experiment was conducted at Bangladesh Institute of Nuclear Agriculture (BINA), Horticulture Division farm, BINA, Mymensingh on effect of different accessions on yield contributing characters and yield of strawberry under different growing conditions during October, 2016 to April, 2017. The twofactor experiment had two levels of planting conditions (Factor A) and three strawberry accessions (Factor B) as follows –Factor A- Planting conditions: a) pot condition and b) field condition and Factor B – strawberry accessions: accession-1( RABI strawberry-1), accession-2 (New York, USA) and accession-3(Kagawa, Japan). The experiment was conducted in randomized complete block design with 3 replications. Results showed that accession-2 revealed the highest results almost all yield contribution characters and yield parameters. The tallest plant (29.78 cm), the highest number of leaves (46.35), longest leaf (26.58 cm), no. of inflorescences (15.95), number of flowers per inflorescence (8.21), number of fruit per inflorescences (7.45), diameter of fruit (4.25 cm), fresh weight of fruit (22.17 g), total soluble solids (18.54 %), yield (g/plot) (400.3 g) and yield per hectare (21.72 t/ha) were recorded from accession-2. But number of seeds per fruit (217.0) was observed from accession -1. The lowest values were found on all the mentioned parameters in accession-3.The significant difference between the growing conditions was observed on all the mentioned parameters. The highest yield (20.12 t/ha) per hectare and yield contributing characters were noted in field condition and the lowest values on all the mentioned parameters were obtained in pot condition. Statistically significant variations were found on all the mentioned parameters due to combined effect. The tallest plant (30.33 cm), highest number of leaves per plant (47.36), longest leaf (27.64 cm), number of inflorescences (16.66), number of flowers per inflorescences (8.99), number of fruit per inflorescences (7.68), individual weight of fruit (25.19 g), total soluble solids (18.98), yield per plot (482.6 g), yield per hectare (24.37t/ha) were found in accession-2 under field condition. The highest diameter of fruit (4.50 cm) was found in accession-3 in field condition which was statistically similar with accession-2 both in field condition and pot condition. The maximum number of seeds per fruit (217.0) was recorded from accession-3 both in pot and field condition. But accession-2 gave the minimum number of seeds per fruit (118.0) under field condition. Res. Agric., Livest. Fish.6(2): 171-179, August 2019